Martial Arts of the World: An Encyclopedia of History and Innovation - Rosa, Vítor (Revista de Artes Marciales Asiáticas, 2012)
Thomas A. Green & Joseph R. Svinth (Eds.). Santa Bárbara (California): ABC-CLIO, 2010. 2 vos. 732 páginas. 26x18 cm. I.S.B.N.: 978-1-59884-243-2.